Perancangan Alat Pembaca Aksara Jawa Pada Prasasti Dengan Metode YOLO - Ubaidillah, Achmad; Fiqhi Ibadillah, Achmad; Lailatul Riski, Ulfa; Fajar Sidik, Rahmad; Kholida, S. Ida (Rekayasa, 2025)
Understanding the history of a nation is very important. Inscriptions are an important historical relic for the nation. Inscriptions provide information and learning for future generations. Inscriptions are usually made of stone or metal. There are several problems in reading the inscription, such as smearing which affects the readability of the writing, erosion of the smear or other things which reduce the legibility of the inscription. On the other hand, Javanese script is a way of writing Javanese instead of using Latin script. It is quite difficult to understand and memorize Javanese script because of its shape and rarely used. Archaeologists in Indonesia generally use fairly simple tools to read inscriptions so it takes a long time. This adds complexity to the process of documenting existing inscriptions. Therefore, in this research a tool was designed to read and translate inscriptions using the principle of light reflection. This is the main contribution and novelty of this research. The data that has been obtained is then processed using image processing and interpreted from Javanese to Indonesian. The method used is YOLO (You Only Look Once) to process image processing. Adding light around the inscription using LED strip lights. From the experiment, the success rate was 88.5% and the failure rate was 11.5%. The intensity of the light and the accuracy of the angle of incidence of the light greatly influence the level of success in reading the writing on the inscription.